Editors' Note: NfL as Analogue of C-Reactive Protein in Neurologic Diseases: Instructions for Use. (8th November 2022) - Siegler, James E.; Galetta, Steven
Abstract : In recent decades, with advances in immunoassays and complementary neurodiagnostic testing, the serum neurofilament light chain (NfL) has emerged as a sensitive biomarker of CNS injury. As a protein that originates exclusively from CNS tissue, Drs. Gaetani and Parnetti contend its presence in the serum indicates nonspecific breakdown of neuronal damage. Therefore, the NfL has been referred to as the "C-reactive protein" (CRP) of neurology. Dr. Ziemssen cautions the analogy of NfL as the CRP of neurologic illness as it may mislead clinicians to believe an inflammatory neurologic condition may be present because the CRP represents a nonspecific inflammatory state. It may be more accurate to compare NfL with serum transaminases as biomarkers of liver injury or troponins as biomarkers of cardiac injury as suggested in this exchange. Whatever the analogy, the take-home message is that neurologists may benefit from leveraging this increasingly available biomarker in neurodiagnostic screening and follow-up.